Low frequency variants associated with leukocyte telomere length in the Singapore Chinese population - Xuling Chang (Nature Portfolio, 2021)
Xuling Chang et al. study whether low frequency variants are associated with leukocyte telomere length and whether these variants predispose to incident cancers and mortalities among East Asians. They find that three East Asian specific variants at POT1, TERF1 and STN1 loci are associated with leukocyte telomere length and report a mechanistic pathway linking TERF1, leukocyte telomere length and incident colon cancer.